Diagnostic Utility of Touch Imprint Cytology of Image Guided Core Needle Biopsy - Dahal, Mona; Karki, Smriti; Regmi, Niraj; Devkota, Karun; Jain, Neetu (Journal of Nobel Medical College, 2023)
Background: Touch imprint cytology of image guided core needle biopsy implies gentle rolling of core needle biopsy obtained with the aid of imaging modality from various organs. The aim of the study was to measure the diagnostic accuracy of touch imprint cytology of image guided core needle biopsy in comparison to histopathological diagnosis. Materials and Methods: A prospective descriptive cross-sectional study was conducted among 47 touch imprint cytology of image guided core needle biopsy in the department of pathology of a tertiary care centre between 1st October 2021 to 30th September 2022 after receiving ethical approval from the institutional review committee. The Papanicolaou and Giemsa-stained slides of touch imprint smear and haematoxylin - eosin-stained slides of core needle biopsy was analysed for adequacy and categorization as non-neoplastic, benign, atypical and malignant. Convenience sampling was done. Results: The most frequent site of image guided core needle biopsy was lung (40.4%). The adequacy rate of touch imprint cytology of image guided core needle biopsy was 85.1%. Among 40 cases of adequate touch imprint smear, 28 cases (70%) were categorized as malignant. The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of touch imprint cytology for categorizing a malignant lesion was 91.18%, 95.45%, 96.88%, 87.5% and 92.86% respectively. Conclusion: The touch imprint cytology of image guided core needle biopsy is a useful modality for the rapid preliminary diagnosis of lesions of various organs with decreased turnaround time for diagnostic workup and ancillary studies.